Simulation of soft-switching converter topology for switched reluctance motor - Sulaiman, M. Yusof; Mohd. Kamil, Ithnaini; Ramli, Abd. Rahman (2005)
Switched Reluctance Motor (SRM) is receiving significant attention from industries in the last decade. SRM is a doubly salient motor with high efficiency. Its geometry is simple, rugged and robust. The absence of the magnet makes the cost of the motor cheaper than any other motor. The life span of SRM is also longer because no brushes are needed. However, the control is complicated because the magnetic properties are non-linear. In this paper a soft-switching inverter topology is introduced and the principle of operation is described. The validity of the topology is verified through simulation.